Testing the Granger noncausality hypothesis in stationary nonlinear models of unknown functional form - Anne Péguin-Feissolle; Birgit Strikholm (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
In this paper we propose a general method for testing the Granger noncausality hypothesis in stationary nonlinear models of unknown functional form. These tests are based on a Taylor expansion of the nonlinear model around a given point in a sample space. We study the performance of our tests by a Monte Carlo experiment and compare these to the most widely used linear test. Our tests appear to be well-sized and have reasonably good power properties.
Keywords: C22; C51; 330; Hypothesis testing; causality; Kausalanalyse; Zeitreihenanalyse; Monte-Carlo-Methode; Simulation; Konjunktur; Theorie